Creation of 'Rentak Sumut' Dance Music As A Tourism Icon of North Sumatra - Herna Hirza; Mukhlis Mukhlis; Ifwanul Hakim; Suharyanto Suharyanto (Universitas Negeri Medan, 2022)
This research work aims to findout a new method of creating dance music 'Rentak Sumut' which is rooted in music local traditions of North Sumatra. The objectives of this research are to finding the method of creating dance music 'Rentak Sumut' as an icon of Sumatran tourism North and finding the method of promoting dance music 'Rentak Sumut' as an icon North Sumatra tourism. The method used in this research is a qualitative approach. The process of searching for data and information is carried out with the interview method deeply to the traditional musician of North Sumatra as informants. The study found that ‘Rentak Sumut’ dance music uses a dance rhythm that comes from music Malay tradition in the 6/8 bar with a medium tempo. Song lyrics describe nature, culture and geography of North Sumatra entirely. North Sumatra Rentak dance music is applied in various communities.